CircRNA_100876 Is Upregulated in Gastric Cancer (GC) and Promotes the GC Cells’ Growth, Migration and Invasion via miR-665/YAP1 Signaling - Lin, Xiaosheng; Huang, Cong; Chen, Zhian; Wang, Huaiming; Zeng, Yongming (Frontiers in Genetics, 2020)
The present study aimed to investigate the biological function and relative mechanisms of circRNA_100876 in gastric cancer (GC). To this end, quantitative real-time polymerase chain reaction (RT-qPCR) was performed to examine the expression of circRNA_100876 and miR-665 in GC tissues and cells, and circRNA_100876 expression was depleted by the transfection of circ_100876-targeting siRNAs. CCK-8, flow cytometry, and Transwell assays were applied to examine GC cell cycle distribution, proliferation, apoptosis, migration, and invasion abilities. Proteins related to apoptosis and epithelial-mesenchymal transition (EMT) were detected by western blotting. Luciferase reporter assays were conducted to verify the direct target site between circRNA_100876 and miR-665. Our study confirmed that circRNA_100876 was highly expressed in GC lesions compared with the adjacent normal tissues (P< 0.001). High circRNA_100876 expression was negatively associated with survival outcome (P=0.000). Furthermore, the down-regulation of circRNA_100876 could inhibit GC cell proliferation, invasion, and migration by suppressing the EMT pathway. Further study suggested that circRNA_100876 could act as a competing endogenous RNA by sequestering miR-665, and luciferase activity assay indicated that circRNA_100876 could bind directly with miR-665. Moreover, we found that Yes-associated protein 1 (YAP1) was the downstream target gene of miR-665, miR-665 knockdown could up-regulate YAP1 expression in MKN45 cells, and YAP1 knockdown could inhibit MKN45 cell proliferation, migration and invasion. Therefore, we demonstrated that circRNA_100876 over-expression in GC could promote GC tumor growth, migration and invasion and exert its effects through miR-665/YAP1 signaling.